Analysis of Green Banking Sustainability And Financial Performance Implementation Towards Profitability of Banking Listed On The Indonesia Stock Exchange In 2012-2018 - Siahaan, Christy; Silalahi, Amlys Syahputra; Syahyunan, Syahyunan; Sianipar, Aryanti Sariartha (TALENTA Publisher, Universitas Sumatera Utara, 2021)
This study aims to determine the impact of green banking and financial performance on bank profitability. Green banking in this study is divided into two dimensions, namely, non-cash transactions (e-banking) and green banking policies. The financial performance in this study is the size of the bank, capital adequacy, non-performing loans, bank efficiency and bank liquidity level. The population in this study was 43 banking sector companies listed on the Indonesia Stock Exchange for the 2012-2018 period. The samples in this study were 9 selected banks using the purposive sampling method.Â The analysis method in this study is panel data regression analysis. The results show that Non-Cash Transactions, Capital Adequacy, Non-Performing Loans and Liquidity Levels of banks each have a negative and insignificant effect on the bank's profitability. Green banking policy has a positive and insignificant effect. Bank Size and Bank Efficiency each negatively and significantly affect the bank's profitability.